Role of Phytobiotics in Modulating Transcriptomic Profile in Carps: A Mini-Review - Wei, Lee Seong; Téllez-Isaías, Guillermo; Abdul Kari, Zulhisyam; Tahiluddin, Albaris B; Wee, Wendy; Kabir, Muhammad Anamul; Abdul Hamid, Noor Khalidah; Cheadoloh, Romalee (Springer Science and Business Media LLC, 2024)
Carp is a key aquaculture species worldwide. The intensification of carp farming, aimed at meeting the high demand for protein sources for human consumption, has resulted in adverse effects such as poor water quality, increased stress, and disease outbreaks. While antibiotics have been utilized to mitigate these issues, their use poses risks to both public health and the environment. As a result, alternative and more sustainable practices have been adopted to manage the health of farmed carp, including the use of probiotics, prebiotics, phytobiotics, and vaccines to prevent disease outbreaks. Phytobiotics, being both cost-effective and abundant, have gained widespread acceptance. They offer various benefits in carp farming, such as improved growth performance, enhanced immune system, increased antioxidant capacity, stress alleviation from abiotic factors, and enhanced disease resistance. Currently, a focal point of research involves employing molecular approaches to assess the impacts of phytobiotics in aquatic animals. Gene expression, the process by which genetic information encoded is translated into function, along with transcription profiling, serves as a crucial tool for detecting changes in gene expression within cells. These changes provide valuable insights into the growth rate, immune system, and flesh quality of aquatic animals. This review delves into the positive impacts of phytobiotics on immune responses, growth, antioxidant capabilities, and flesh quality, all discerned through gene expression changes in carp species. Furthermore, this paper explores existing research gaps and outlines future prospects for the utilization of phytobiotics in aquaculture.
Keywords: Carps; Probiotics; Animals; Aquaculture; Transcriptome; Antioxidants